Flexible electrical stimulation device with Chitosan-Vaseline® dressing accelerates wound healing in diabetes - Wang, Xiao-Feng; Li, Meng-Lu; Fang, Qing-Qing; Zhao, Wan-Yi; Lou, Dong; Hu, Yan-Yan; Chen, Jun; Wang, Xiao-Zhi; Tan, Wei-Qiang (Bioactive materials, 2021)
The healing process of diabetic wounds is typically disordered and prolonged and requires both angiogenesis and epithelialization. Disruptions of the endogenous electric fields (EFs) may lead to disordered cell migration. Electrical stimulation (ES) that mimics endogenous EFs is a promising method in treating diabetic wounds; however, a microenvironment that facilitates cell migration and a convenient means that can be used to apply ES are also required. Chitosan-Vaseline® gauze (CVG) has been identified to facilitate wound healing; it also promotes moisture retention and immune regulation and has antibacterial activity. For this study, we created a wound dressing using CVG together with a flexible ES device and further evaluated its potential as a treatment for diabetic wounds. We found that high voltage monophasic pulsed current (HVMPC) promoted healing of diabetic wounds in vivo. In studies carried out in vitro, we found that HVMPC promoted the proliferation and migration of human umbilical vein endothelial cells (HUVECs) by activating PI3K/Akt and ERK1/2 signaling. Overall, we determined that the flexible ES-chitosan dressing may promoted healing of diabetic wounds by accelerating angiogenesis, enhancing epithelialization, and inhibiting scar formation. These findings provide support for the ongoing development of this multidisciplinary product for the care and treatment of diabetic wounds. [Display omitted] •High voltage monophasic pulsed current (HVMPC) is the relatively optimal parameter to improve diabetic wounds healing.•HVMPC promotes the proliferation and migration capacity of human umbilical vein endothelial cells (HUVECs).•Chitosan-Vaseline® gauze (CVG) promotes the healing of diabetic wounds for providing a good microenvironment.•The flexible electrical stimulation (ES) chitosan dressing is a therapeutic method for diabetic wound treatments.